Hubungan Panjang Jari Telunjuk Tangan (Digiti II Manus) Terhadap Tinggi Badan Pada Suku Batak Di Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Mubela, Dewi Kartika; Sutysna, Hendra (Sriwijaya Journal of Medicine, 2020)
There are several accidents when the bodies of victims from natural disasters or disaster from human error cannotbe identified because of severe damage and only be found a few parts of the body. The estimated length of the body can be done by measuring a certain part of body to estimate height. The regression formula using the length of the index finger of the hand, age and sex has been proofed as valid estimate of the height and is useful in clinical context. The aim of this study wasto determine the relation of middle finger length to stature of Bataknese at the Faculty of Medicine Universitas Muhammadiyah Sumatera Utara (UMSU). This study was a descriptive correlative study with cross-sectional design. The population was students, permanent lectures, and education staffs from Bataknese at the Faculty of Medicine UMSU who had completed the inclusion and exclusion criterias. The sampling technique used total sampling method with the total subject was 63 people. Index finger length was positively and significantly correlated to stature with coefficient correlation ranging from 0.611 to 0.681 (p<0.001). Linear regression equations were showing Standard Error of the Estimate (SEE) ranging from 2.883 to 3.3839 (p<0.001). There was significantly relation of index finger length to stature with strong and very strong correlation, so the stature can be estimated by measuring index finger length with linear regression equation.